Vesicouterine Fistula (VUF) as a Rare Urogenital Complication Managed with Delayed Surgical Repair: A Case Report and Review of the Literature - Evangelos N. Symeonidis; Elias Sdralis; Asterios Symeonidis; Christos Georgiadis; Vasileios Kalyvas; Apostolos Malioris; Michail Papathanasiou (Hindawi Limited, 2018)
Vesicouterine fistula (VUF) represents a rare urogenital complication. It is considered to be the least common type of urogenital fistulas. Iatrogenic reasons have been shown to be the most prominent cause, with lower segment caesarean section accounting for approximately two-thirds of the cases. The highest incidence concerns young females of reproductive age. VUF can present with clinical symptoms varying from cyclic hematuria, amenorrhea, and vaginal leakage of urine to secondary infertility and first-trimester abortion. Quality of life (QoL) for patients having this pathology is strongly affected due to the psychological burden. Surgical excision of the fistula remains the mainstay of treatment, as less than 5% of patients respond to conservative therapy. Recently laparoscopic and robotic-assisted VUF repair started gaining ground with comparable results to open surgery. Herein, we presented the successful delayed surgical repair of VUF in a 32-year-old female patient. A review of the published literature was also performed, summarizing all the available evidence regarding this rare clinical entity.